Pengaruh Pajak Kendaraan Bermotor (PKB), Bea Balik Nama Kendaraan Bermotor (BBN-KB), dan Pajak Air Permukaan (PAP) terhadap Pendapatan Asli Daerah pada UPTD Pependa Di Provinsi Sumatera Utara - Sihaloho, Yana Kumala Sari; Dewi, Ratna Sari; Fauzi, Indra; Lubis, Reza Hanafi (Jurnal EMT KITA, 2025)
The purpose of this research is to determine the effect of Motor Vehicle Tax (PKB), Vehicle Transfer Duty (BBN-KB), and Surface Water Tax (PAP) on Regional Original Income (PAD) at UPTD PEPENDA in North Sumatra Province. The research method used is a quantitative method, which means an approach in research that uses numerical data. The sampling in this study uses Purposive Sampling, where samples are selected based on specific goals or characteristics deemed relevant to the research. The characteristics that have financial data from UPTD PEPENDA include data on Realization of Motor Vehicle Tax (PKB), Vehicle Transfer Duty (BBNKB), Surface Water Tax (PAP), and Regional Original Income (PAD). The data used is secondary data in a time series from 2021 to 2023 from UPTD Pependa in North Sumatra Province. The research results indicate that Motor Vehicle Tax has an effect on Local Own Revenue in North Sumatra Province, while Vehicle Name Transfer Fee does not affect Local Own Revenue in North Sumatra Province, and Surface Water Tax has an effect on Local Own Revenue in North Sumatra Province. PKB, BBNKB, and PAP collectively influence Local Own Revenue in North Sumatra. PKB, BBNKB, and PAP have a strong relationship with PAD, which is 0.913, meaning that PKB, BBNKB, and PAP account for 91.3% of PAD in North Sumatra Province, while the remaining 8.7% is influenced by other factors not included in this research.